A bipartite NLS motif mediates the nuclear import of Drosophila moesin - Kovács, Zoltán; Bajusz, Csaba; Szabó, Anikó; Borkúti, Péter; Vedelek, Balázs; Benke, Réka; Lipinszki, Zoltán; Kristó, Ildikó; Vilmos, Péter (Frontiers in Cell and Developmental Biology, 2024)
The ERM protein family, which consists of three closely related proteins in vertebrates, ezrin, radixin, and moesin (ERM), is an ancient and important group of cytoplasmic actin-binding and organizing proteins. With their FERM domain, ERMs bind various transmembrane proteins and anchor them to the actin cortex through their C-terminal F-actin binding domain, thus they are major regulators of actin dynamics in the cell. ERMs participate in many fundamental cellular processes, such as phagocytosis, microvilli formation, T-cell activation and tumor metastasis. We have previously shown that, besides its cytoplasmic activities, the single ERM protein of Drosophila melanogaster, moesin, is also present in the cell nucleus, where it participates in gene expression and mRNA export. Here we study the mechanism by which moesin enters the nucleus. We show that the nuclear import of moesin is an NLS-mediated, active process. The nuclear localization sequence of the moesin protein is an evolutionarily highly conserved, conventional bipartite motif located on the surface of the FERM domain. Our experiments also reveal that the nuclear import of moesin does not require PIP2 binding or protein activation, and occurs in monomeric form. We propose, that the balance between the phosphorylated and non-phosphorylated protein pools determines the degree of nuclear import of moesin.